Object Phobia and Altered RhoA Signaling in Amygdala of Mice Lacking RICH2 - Sarowar, Tasnuva; Grabrucker, Stefanie; Boeckers, Tobias M.; Grabrucker, Andreas M. (Frontiers in Molecular Neuroscience, 2017)
RICH2 knockout (RICH2 KO) mice exhibit neophobia in the novel object test. To gain further insight into their anxiety-related phenotype, we subjected these mice to additional behavioral tests to elucidate whether the behavioral abnormality in these mice is a consequence of reduced exploratory motivation, and whether the neophobia is linked specifically to objects or also present for other modalities. RICH2 KO mice engage in normal exploration in a novel environment, suggesting that the anxiety-related phenotype is not due to reduced exploratory drive. Increased fear response was not observed using novel olfactory cues, but restricted to objects. Given that the amygdala is an important brain region mediating anxiety-related behaviors and a prime target for anxiety-related therapeutics, and RICH2 is a Rho-GAP protein regulating synaptic spine plasticity via small GTPases, we analyzed spine formation, morphology and receptor composition in amygdala. We found disinhibition of RhoA in the amygdala of RICH2 KO mice, along with a decreased ability for actin polymerization and a reduction in mature spines. However, we detected increased neuronal activation in the amygdala evidenced by c-fos labeling. Thus, we conclude that despite unaltered baseline activity, RICH2 KO mice show heightened amygdala response after exposure to objects, which, however, does not result in homeostatic strengthening of excitatory synapes.